2008
DOI: 10.1148/radiol.2491071650
|View full text |Cite
|
Sign up to set email alerts
|

Airway Dimensions at Inspiratory and Expiratory Multisection CT in Chronic Obstructive Pulmonary Disease: Correlation with Airflow Limitation

Abstract: Airway lumen measured at expiratory CT was more closely related to expiratory airflow measurements than was lumen measured at inspiratory CT. In addition, the changes of airway luminal area between inspiration and expiration were strongly related to airflow limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
109
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 28 publications
14
109
2
Order By: Relevance
“…At this point, our results suggest that airflow limitation could be located behind the third generation bronchi as reported already by Matsuoka et al (14). However, these authors did not examined all segmental and subsegmental bronchi which limits in our opinion the validity of such statements as the bronchial system is expected to underlie some regional variations in terms of luminal collapsibility dictated by the local anatomy and physiologic influence of thoracic cage mobility.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…At this point, our results suggest that airflow limitation could be located behind the third generation bronchi as reported already by Matsuoka et al (14). However, these authors did not examined all segmental and subsegmental bronchi which limits in our opinion the validity of such statements as the bronchial system is expected to underlie some regional variations in terms of luminal collapsibility dictated by the local anatomy and physiologic influence of thoracic cage mobility.…”
supporting
confidence: 82%
“…Other reports suggested that airflow limitation in COPD was closely related to the airway dimensions from the 3 rd to the 6 th generation bronchi (13). Again previous reports have asserted that airway dimensions of the large-and intermediate-sized airways reflect airway dimensions in the smaller airways, which are the most important site of airway obstruction in COPD (7,14). The compliance of the extra-and intrapulmonary airways depends finally both on the mechanical structure (bronchial wall characteristics) as well as on the quality of lung parenchyma surrounding the bronchial tree (23).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Morphometric bronchoscopy is also useful for identifying and quantifying fixed and variable CAO 20,29 ; however, image analysis is not performed immediately, but post-procedure, with image processing software. Immediate quantification of the degree of CAO might be achieved in the future, with stereoscopic bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional area at the narrowest bronchial segment was measured with CT analysis software (Ziostation, Ziosoft, Tokyo, Japan). 20 …”
Section: Computed Tomographymentioning
confidence: 99%